2012
DOI: 10.3109/13816810.2012.681096
|View full text |Cite
|
Sign up to set email alerts
|

Reduced L- and M- and increased S-cone functions in an infant with thyroid hormone resistance due to mutations in theTHRβ2gene

Abstract: We document a congenital disorder of cone function characterized by severely reduced L- and M-cone responses and increased S-cone responses caused by deleterious mutations in the THRβ2 gene in thyroid resistant patients. Thyroid hormone, via TRβ2, is critical for determining cone-type differentiation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…This is in agreement with the observations in a human patient carrying TRβ2 mutations. This patient merely showed red/green color complications but rod morphology and rhodopsin expression level remained normal (32). In this study, we found no negative effect of antithyroid treatment on rod survival in our degenerating mouse models.…”
Section: Discussionmentioning
confidence: 46%
“…This is in agreement with the observations in a human patient carrying TRβ2 mutations. This patient merely showed red/green color complications but rod morphology and rhodopsin expression level remained normal (32). In this study, we found no negative effect of antithyroid treatment on rod survival in our degenerating mouse models.…”
Section: Discussionmentioning
confidence: 46%
“…Also, albeit rare, male patients are color blind in TH resistance syndrome, which represents a model for fetal hypothyroidism. In a case report, reduced L-and M-and increased S-cone functions in an infant with TH resistance due to mutations in the THRβ2 gene were demonstrated [21] . However, neither fetal hypothyroidism nor preterm infant studies may serve as appropriate models for adult hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies in mice have successfully addressed the implications of these mutations in humans. 83 …”
Section: Thyroid Hormone Receptorsmentioning
confidence: 99%